(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
From December 1997 to March 1999 samples of leaves infested by Citrus Leaf Miner Phyllocnistis citrella (CLM)_Stainton were collected in several citrus groves around Palermo in arder to bred indigenous parasitoids. Among the different species of Eulophid wasps emerged also: Asecodes delucchii (Boucek), Baryscapus sp., Elasmus sp., Aprostocetus sp.. This latter species was also obtained by Stigmella sp. on Ulmus sp .. In Italy these parasitoids were not known to attack the already mentioned Gracillariid. Among those already known all developmental stages of Semielacher petiolatus (Girault) were observed during winter 1998-1999. These records highlight a probable permanent establishment of this parasitoid in the Sicilian citrus groves. With the aim of strengthening the natural biological control against the CLM, a strain of Citrostichus phyllocnistoides (Narayanan) introduced from Jordan is now bred in arder to support its releases into citrus groves of the Island.